SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE SMART UNTUK PEMILIHAN SISWA TERBAIK - Purwanto, Heru; Ishak, Riswansi; Pangesti, Witriana Endah; Saefulloh, Asep; Suharyanto, Suharyanto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Determining the best students in the school environment is an important part of providing recognition and motivation to students. This selection process must be conducted objectively, fairly, and transparently so that the results can be accepted by all parties. This research aims to implement the SMART (Simple Multi-Attribute Rating Technique) method to decision system making in selecting the best students at SMK Bhakti Bangsa. The criteria used include report card grades, attendance, attitudes, extracurricular activity participation, and non-academic achievements in competitions at the national, district, or sub-district levels. The results of the implementation indicate that the SMART method can assist in the evaluation process systematically and lead to more accurate decisions.